ミズホ カンソク キョテン ノ ニッシャ シュウシ - 川口, 貞男; カワグチ, サダオ; 佐々木, 浩; ササキ, ヒロシ; KAWAGUCHI, Sadao; SASAKI, Hiroshi (国立極地研究所, 1975)
P(論文) The solar radiation balance on the ground surface at Mizuho Camp (70°42.6'S, 44°18.9'E, elevation 2,200m) is discussed on the basis of the observations with two pyranometers carried out during the period from July to December 1972. The daily values of the global radiation around the summer solstice were 950 Ly under clear sky, and 640 Ly when cloudy, giving a monthly total of 25.6 × 10^3 Ly for December. Averaged monthly values of the albedo varied from 0.86 to 0.83 in July to December, and the albedos under cloudy condition were somewhat larger than those under clear sky condition. The decrease of the global radiation by cloud cover was small, about 30%, in comparison with the case in lower latitudes. This is partly due to the high transmissibility of clouds in Antarctica, and partly due to the multiple reflection of the solar radiation between the cloud bottom and the snow surface which has large albedos. The monthly values of global radiation and albedo for January to June in 1972 were estimated; relations among the solar altitude, global radiation and albedo obtained in the observed months were taken into consideration, extrapolating the observed cloud amounts at Syowa Station (69°00'S, 39°35/E) to Mizuho Camp. The annual values of global radiation and the effective short-wave radiation were 114×10^3Ly and 19 × 10^3 Ly, respectively. departmental bulletin paper